Foot Pain, Impairment and Disability in Patients With Acute Gout Flares; A Prospective Observational Study - Rome, K; Frecklington, M; Rome, K; McNair, PJ; Gow, P; Dalbeth, N (John Wiley & Sons, 2011)
Objectives: The aim of this study was to evaluate the impact of acute gout on foot pain, impairment and disability. Methods: This prospective observational study recruited 20 patients with acute gout flares. Patients were recruited from emergency departments, hospital wards and rheumatology outpatient clinics throughout Auckland, New Zealand. Patients were recruited at the time of the flare (baseline visit) and then reassessed at a follow-up visit once the acute flare had resolved 6-8 weeks after the initial assessment. Joint counts, C-reactive protein and serum urate were recorded at both visits. General and foot-specific outcome measures were also recorded at each visit including pain visual analogue scale, Health Assessment Questionnaire (HAQ)-II, Lower Limb Tasks Questionnaire, and the Leeds Foot Impact Scale. Results: The foot was affected by acute gout in 14 (70%) patients. Objective measures of joint inflammation including swollen and tender joint counts and C-reactive protein significantly improved at the follow-up visit, compared with the baseline visit. At baseline, high levels of foot pain, impairment and disability were reported. All patient-reported outcome measures of general and foot-specific musculoskeletal function improved at the follow-up visit compared with the baseline visit. However, pain, impairment and disability scores did not entirely normalise after resolution of the acute gout flare. Conclusions: Patients with acute gout flares experience severe foot pain, impairment and disability. These data provide further support for improved management of gout to prevent the consequences of poorly controlled disease.
Keywords: Gout; Pain; Foot; Disability; Joint; Outcome measures